2004
DOI: 10.2337/diabetes.53.12.3233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Administration of α-Lipoic Acid on Retinal Capillary Cell Death and the Development of Retinopathy in Diabetic Rats

Abstract: Oxidative stress is increased in the retina in diabetes, and it is considered to play an important role in the development of retinopathy. ␣-Lipoic acid, a thiol antioxidant, has been shown to have beneficial effects on polyneuropathy and on the parameters of oxidative stress in various tissues, including nerve, kidney, and retina. The purpose of this study was to examine the effect of ␣-lipoic acid on retinal capillary cell apoptosis and the development of pathology in diabetes. Retina was used from streptozo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
233
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(244 citation statements)
references
References 43 publications
9
233
1
1
Order By: Relevance
“…The role of ROS in 'memory' of high glucose stress in diabetic retina The next experiment was to determine whether the persistence of hyperglycaemic stress could be interrupted in the rat diabetic model in vivo, using the mitochondrial antioxidant nutritional supplement, ALA, which has previously been shown to interrupt target organ damage when given chronically to diabetic animals [20]. The addition of ALA to the last week of normalised glucose resulted in significant decreases in most of the hyperglycaemic stress markers in the retina of diabetic animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of ROS in 'memory' of high glucose stress in diabetic retina The next experiment was to determine whether the persistence of hyperglycaemic stress could be interrupted in the rat diabetic model in vivo, using the mitochondrial antioxidant nutritional supplement, ALA, which has previously been shown to interrupt target organ damage when given chronically to diabetic animals [20]. The addition of ALA to the last week of normalised glucose resulted in significant decreases in most of the hyperglycaemic stress markers in the retina of diabetic animals (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Blood glucose levels were in the following ranges: 5.8-8.0 mmol/l in non-diabetic rats, 17-22.8 mmol/l in diabetic rats and 4.8-5.6 mmol/l in the last week of treatment in insulin-treated animals. ALA (racemic mixture; Sigma Chemical) was prepared in 0.9% sodium chloride, pH 7.4, snap-frozen, stored at −80°C and aliquots thawed daily just before injection [20]. Animals receiving ALA were injected intraperitoneally with 75 mg/kg ALA each day, while all other animals received daily injections of 0.9% sodium chloride, pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…While this paper was being prepared, Kowluru and Odenbach published data on the racemic mixture of α-lipoic acid [37]. They showed that the oral administration of 400 mg/kg body weight over 11 months in Wistar rats reduced retinal oxidative stress and the formation of acellular capillaries.…”
Section: Discussionmentioning
confidence: 99%
“…10) (El-Remessy, 2003a;Graier et al, 1999;Graier et al, 1997;Graier et al, 1996) resulting in peroxynitrite formation. Research demonstrating increased levels of the peroxynitrite biomarker nitrotyrosine in retinas of diabetic patients and experimental animal models supports this concept and implies a role for peroxynitrite in the development of diabetic complications (Abu El-Asrar et al, 2004;Du et al, 2002;ElRemessy, 2003b;Kowluru and Odenbach, 2004;Obrosova et al, 2005). Studies in animal and tissue culture models have demonstrated that increased peroxynitrite formation is directly correlated with diabetes, high glucose-induced VEGF expression, and increased retinal vascular permeability (El-Remessy, 2003a;El-Remessy, 2003b;El-Remessy et al, 2006;El-Remessy et al, 2005).…”
Section: Oxidative Stress and Diabetic Retinopathymentioning
confidence: 95%